Diferentes níveis nutricionais para suínos machos: desempenho animal e qualidade da carcaça e da carne - Lanferdini, Eloiza (2012)
The study was carried out to evaluate the performance and carcass and meat quality of surgically castrated, entire male/immunocastrated pigs fed with diets containing different levels of amino acids and energy with or without ractopamine. Seventy two pigs (surgically castrated and entire male/immunocastrated pigs) with average initial weight of 20 kg were used. The animals were distributed in a completely randomized experimental design with four treatments (T1 - surgically castrated pigs fed control diet; T2 - entire male/immunocastrated pigs fed control diet; T3 - entire male/immunocastrated pigs fed control diet + 3% amino acids and energy and T4 - entire male/immunocastrated pigs fed control diet + 5% amino acids and energy), with six replications, and three animals as an experimental unit. The second dose of immunocastration vaccine occurred 28 days before slaughter, at this time 5 ppm of ractopamine was added to the diet of half of the experimental units for each treatment. Twenty four animals were slaughtered (one per experimental unit) selected by experimental unit s average weight. The entire male pigs had feed intake 11% lower (P<0.05) and feed conversion 16% better (P<0.05) compared to surgically castrated. Supplementation with 5% of amino acids and energy reduced (P<0.05) at 6.9% the feed intake and improved (P<0.05) at 3.0% the feed conversion of entire male pigs. Immunocastrated pigs supplemented with 5% of amino acids and energy and 5 ppm ractopamine gained daily 0.13 kg more weight (P<0.05) and feed conversion was 13% better (P<0.05) compared to immunocastrated male pigs fed control diet without ractopamine. The slaughter weight of immunocastrated pigs supplemented with 5% of amino acids and energy was 12% higher (P<0.05) than surgically castrated fed control diet without ractopamine. When don t supplemented with ractopamine, the immunocastrated pigs had carcass yield 5.4% lower (P<0.05) than surgically castrated. Immunocastrated pigs supplemented with 5% of amino acid and energy with ractopamine had higher (P<0.05) weight of the belly and rib and superior value (P<0.05) in color b* (yellow-blue) of meat at 24 hours. Supplementation with 5% of amino acids and energy reduces feed intake, improves feed conversion and slaughter, belly and ribs weight of immunocastrated pigs.